THE EFFECT OF RAFT STRATEGY ON STUDENTS’ WRITING SKILL BY USING WHATSAPP - Amalia Riswanti; Masrul Masrul (Journal of English Language and Education, 2021)
This study was motivated by the number of students who get low scores, especially in writing at 11th grade student of MA MualiminMuhammadiyahBangkinang. RAFT strategy is an effective strategy for overcoming this problem. Based on the problem, this research aims to find out whether there is an effect on using RAFT strategies towards the students writing skill in online class, in academic year 2019/2020. This is a quasi-experimental research. This research involves 46 students of two classes, class XI IPA Putri as the experimental class consists of 23 students and class XI IPA Putra as the control class consists of 23 students. The experimental class using RAFT strategies and control class using Teacher’s method. The data were obtained by using Pre-test and Post-test. Pre-test was given to both classes before the treatment and Post-test of both classes were analyzed by using t-test analysis. Based on the data analysis of the research showed that the average students post-test in experimental class were 72, and control class has average students post-test were 65. Based on the data analysis of variance it can be seen that the significant (2-tailed) of 0.000 which is smaller than 0.05. It can be concluded that there is the effect of RAFT strategies toward students’ writing skill at the eleventh grade of MA MualiminMuhammadiyahBangkinang